Clostridium septicum-infected Stanford type A acute aortic dissection: a case report - Kiyotoshi Akita; Yoshiyuki Takami; Kazuki Matsuhashi; Yusuke Sakurai; Kentaro Amano; Hiroshi Ishikawa; Tadahito Eda; Yasushi Takagi (Surgical Case Reports)
Abstract Background Thoracic aortitis caused by Clostridium septicum is a rare infection with a strong association with malignancy and high mortality rate when left untreated. We report a case of surgical treatment for Stanford type A acute aortic dissection in a patient with C. septicum sepsis and thoracic aortitis. Case presentation A 63-year-old hypertensive man with rheumatoid arthritis presented with general malaise and diagnosed with C. septicum-infected aortitis with sepsis. On the 5th day of hospitalization, Stanford type A acute aortic dissection developed with severe aortic regurgitation. The patient underwent emergent surgical treatment successfully with excision of the infected ascending aorta and aortic root followed by replacement using a composite graft, followed by diagnosis of sigmoid colon cancer 7 months after aortic surgery. He was scheduled to undergo elective colon surgery. Conclusions C. septicum aortitis can progress quickly, causing aneurysm or dissection. Therefore, in a patient with C. septicum aortitis, prompt surgical in situ graft replacement should be performed to debride the infected vascular lesions. Further investigations for gastrointestinal and hematological malignancies as a source of C. septicum should be also conducted.